Bamboo waste recycling using Dictyophora indusiata mycelia cultivation - Haruthai Thaisuchat; Weeranuch Karuehanon; Pornanan Boonkorn; Jumnian Meesumlee; Sarayut Malai; Kanjana Ruttanateerawichien (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Reusing agricultural waste as a substrate material for mushroom cultivation was considered a great alternative to bio-waste disposal. In this study, bamboo waste from a local skewer factory in Lampang Province, Thailand, was used as a substrate, along with the original material for the mycelial growth of Dictyophora indusiata mushroom.Method D. indusiata mycelia were grown in two materials in three different combinations: lingzhi pieces, lingzhi pieces combined with bamboo scraps (1:1), and bamboo scraps. A number of days when the substrate was completely covered with mycelia was recorded. After that, the mycelia from all three cultures were used as inoculum for cultivating D. indusiata through two procedures, including in-field direct cultivation and spawn production before cultivation. To evaluate the mushrooms productivity, the length of time to fruiting and the weight of the harvested mushrooms were recorded.Results D. indusiata mycelia grew fastest in a lingzhi-based substrate (19.3 days), followed by a combination of lingzhi and bamboo (24.9 days) and bamboo (35.7 days). The highest number of the fruiting body (37.0 mushrooms per plot) and fresh weight (2,310.5 g/0.75 m2) were observed in treatments in which spawn was produced prior to cultivation and inoculum was derived from lingzhi pieces combined with bamboo scraps. The next two highest mushroom yields were obtained through cultivation using bamboo scraps inoculum, which required more time to develop.Conclusion Bamboo scrap was a promising material for mycelial growth and cultivation of D. indusiata.